From organoids to organs: Bioengineering liver grafts from hepatic stem cells and matrix. Issue 2 (April 2017) - Willemse, Jorke; Lieshout, Ruby; van der Laan, Luc J.W.; Verstegen, Monique M.A.
Abstract: Due to the complex function and structure of the liver, resourceful solutions for treating end-stage liver disease are required. Currently, liver transplantation is the only curative therapeutic option. However, due to a worldwide donor shortage, researchers have been looking in other fields for alternative sources of transplantable liver tissue. Recent advances in our understanding of liver physiology, stem cell and matrix biology, have accelerated tissue engineering research. Most notable is the discovery of a culture system to grow liver-like organoids from human hepatic stem cells. The extensive expansion capacity of these stem cells has contributed greatly to the availability of hepatocyte-like cells for tissue engineering. In addition, new techniques are explored to obtain biological liver scaffolds from full size donor organs. This review summarizes these state-of-art techniques which may lay the groundwork towards re-creating transplantable tissue from autologous or allogenic stem cells in the coming decade.